2021
DOI: 10.3389/fpsyg.2020.592994
|View full text |Cite
|
Sign up to set email alerts
|

Opportunity Finding by Nascent Entrepreneurs: Accidental or Purposeful?

Abstract: PurposeThis research studies an important, but relatively unexplored entrepreneurial aspect: motivation and aspiration on opportunity finding/discovery.Design/Methodology/ApproachThis study surveyed 230 nascent entrepreneurs on their opportunity finding behavior. A poisson regression and a logistic analysis were conducted to discover the relationship between motivation/aspiration and opportunity search behavior.FindingsMotivation and aspiration interact to influence active search in a positive way. However, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Mainstream nascent entrepreneurship literature associates the motivation to start a business with autonomy, achievement, willingness to become an entrepreneur and wealth aspiration motivations (Zhou and Wu, 2021). For example, Zhou and Wu (2021) found that the need for achievement or for affiliation constitutes the main motives to become an entrepreneur.…”
Section: Intrinsic Drivers Of Nascent Entrepreneurship 31 Entrepreneu...mentioning
confidence: 99%
See 3 more Smart Citations
“…Mainstream nascent entrepreneurship literature associates the motivation to start a business with autonomy, achievement, willingness to become an entrepreneur and wealth aspiration motivations (Zhou and Wu, 2021). For example, Zhou and Wu (2021) found that the need for achievement or for affiliation constitutes the main motives to become an entrepreneur.…”
Section: Intrinsic Drivers Of Nascent Entrepreneurship 31 Entrepreneu...mentioning
confidence: 99%
“…Mainstream nascent entrepreneurship literature associates the motivation to start a business with autonomy, achievement, willingness to become an entrepreneur and wealth aspiration motivations (Zhou and Wu, 2021). For example, Zhou and Wu (2021) found that the need for achievement or for affiliation constitutes the main motives to become an entrepreneur. Furthermore, “need for achievement” motivations influence the types of business start-up decisions and a greater emphasis on financial success, whereas “need for affiliation” is attributed to business start-up for social and community-based objectives (Weerasinghe and Madurapperuma, 2020).…”
Section: Intrinsic Drivers Of Nascent Entrepreneurshipmentioning
confidence: 99%
See 2 more Smart Citations